2011
DOI: 10.1186/1752-1947-5-198
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma in the distal femur two years after an ipsilateral femoral shaft fracture: a case report

Abstract: IntroductionThe duration of symptoms preceding a definitive diagnosis of osteosarcoma is quite long. Pathological radiological signs are often evident by the time of diagnosis. Although several case reports have been published on osteosarcoma of the femur, to the best of our knowledge this report is the first one with such an unusual clinical course.Case presentationWe describe the case of a 58-year-old Caucasian man who presented with a femoral shaft fracture. Two years post-trauma osteosarcoma in the ipsilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It is important to identify possible an underlying malignant tumor in any fracture, especially after trivial injury. A case has been reported with a delayed diagnosis of osteosarcoma 2 years after the femoral shaft fracture 18. Patient had amputation and chemotherapy and was alive without metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to identify possible an underlying malignant tumor in any fracture, especially after trivial injury. A case has been reported with a delayed diagnosis of osteosarcoma 2 years after the femoral shaft fracture 18. Patient had amputation and chemotherapy and was alive without metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patient had amputation and chemotherapy and was alive without metastatic disease. Overlooking a pathological fracture might result in delayed diagnosis, further progression and metastases of the disease 7, 18. Clinicians and radiologists should therefore be aware of the possibility of pathological fracture particularly when there is an atypical mechanism of injury in the history and progressive symptoms despite treatment for simple fracture.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1956, Oppenheimer et al [ 22 ] observed the carcinogenic effect of silver, tantalum, vitallium and stainless steel by subcutaneously embedding metal foils in rats. Clinical studies on the carcinogenicity of metal orthopedic implants showed that a similar tumor category, predominantly sarcomas, developed at the implant site and the latent periods for tumor development ranged from 2 years to more than 30 years [ 23 - 42 ]. The detailed information of these cases was listed in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous trauma in the tumor site has been found to increase osteosarcoma risk. [43,44] [45] Rous sarcoma virus (retrovirus or RNA virus) contains a gene called V-Scr and has a proto-oncogene homologue [Pritchard, 1975]. Previously, with the discovery of the Simian virus 40 (SV40), the viral origin of osteosarcoma was shown with SV40.…”
Section: -Growth and Development Stagementioning
confidence: 99%